Reformasi Pendidikan di Indonesia Perspektif Muhammadiyah - Eni Latifah (Istitut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2015)
One of the socio-religious organization that is concerned with the education of Muhammadiyah. This organization from the beginning was designed to meajukan dignity of Muslims through various media, especially education. Anxiety arises, because the founder of Muhammadiyah realize that Islamic educational institutions that existed at that time was less able to respond to the challenges of the times and simply emphasize the religious education ansich. As a result, Muslims are backward in all fields of fact, the religious dimension is clearly not just a matter of religion but also a social problem and nature. Islamic religion openly have stated that the teachings are complete, perfect and will always be in accordance with the circumstances and conditions Any and, wherever and until whenever. This signifies that all dimensions of life have been covered in Islam. therefore, the Muslims have an obligation to learn and master the science of religion, social sciences and natural sciences Muslims to be developed. However, due to various factors, then the people before the establishment of Muhammadiyah education focuses only on religious knowledge alone. As a result, Muslims are in a state of backwardness and oppression. As an institution reformer, the Muhammadiyah also perform a wide berbaga renewal in the field of education. This article will focus on the study of the educational reform ala Muhammadiyah to respond to the challenges of the times.